Covid-19 in American Political Speeches: A Discourse Analysis - Katea , Haider Hussein; Hassan, Noor Abdulnabi (Journal of Ecohumanism, 2024)
During the time of COVID-19, politicians around the world delivered different ideological speeches. The study in hand aims at identifying the types and triggers presupposition that exist in American political COVID-19 speeches. This is to uncover the crucial role that linguistic factors in shaping political leaders’ communication strategies during pandemics. Particularly, how preferences and implicit motivations are expressed. In doing this, the study limits itself to analyses presupposition in political speeches delivered by four key figures — Governor Gavin Newsome, Governor Andrew Cuomo, Secretary Anthony Blinken, and Secretary Alex Azar — during the COVID-19 pandemic. Methodologically, the analysis draws on Yule (1996) and Levinson (1983). The results show that lexical presuppositions are the most frequently encountered, followed by structural and existential presuppositions, besides a variety of types of presuppositions triggers used in discourses.